2010
DOI: 10.1002/art.30082
|View full text |Cite
|
Sign up to set email alerts
|

In vivo fluorescence imaging of E‐selectin: Quantitative detection of endothelial activation in a mouse model of arthritis

Abstract: Objective. In vivo optical imaging can delineate at the macroscopic level processes that are occurring at the cellular and molecular levels. E-selectin, a leukocyte adhesion molecule expressed on endothelium, is induced by tumor necrosis factor ␣ (TNF␣) and other cytokines involved in the pathogenesis of rheumatoid arthritis (RA). Collagen-induced arthritis (CIA) in mice is widely used to study the disease mechanisms and identify new treatments for RA. The purpose of this study was to demonstrate E-selectin-ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…In CIA, E-selectin-targeted optical imaging has been demonstrated to reflect inflammatory activity with similar SNR to our data29. Interestingly, S100A9 has been shown to induce the expression of E-selectin in endothelial cells30, indicating that both methods address different target cells within closely linked inflammatory mechanisms.…”
Section: Discussionsupporting
confidence: 79%
“…In CIA, E-selectin-targeted optical imaging has been demonstrated to reflect inflammatory activity with similar SNR to our data29. Interestingly, S100A9 has been shown to induce the expression of E-selectin in endothelial cells30, indicating that both methods address different target cells within closely linked inflammatory mechanisms.…”
Section: Discussionsupporting
confidence: 79%
“…In addition, 64 Cu antibodies were able to visualize glucose-6-phosphate isomerase in joints of mice from the K/BxN mouse model of arthritis using small-animal PET (28). More specific attention was paid to markers associated with inflammatory conditions in studies using near-infrared antibody-guided imaging to visualize E-selectin (29), present on activated endothelium, and F4/80 (30), present on macrophages and eosinophils. Furthermore, Turk et al demonstrated accumulation of activated macrophages in joints of rats with adjuvant-induced arthritis by g-scintigraphy using folic acid-99m Tc conjugates, which bind to the high-affinity folate receptor (31).…”
Section: Discussionmentioning
confidence: 99%
“…These mechanisms commence early in the pathogenesis of arthritis. Fluorescently labeled anti-E-selectin antibodies were successfully used for imaging in a mouse model for RA, enabling detection of subclinical manifestations, monitoring effects of therapy, and quantification of disease [61]. In patients with RA, 99m Tc-anti-E-selectin-Fab appeared to be suitable for scintigraphic imaging of synovitis and showed a higher specificity than 99m Tc- hydroxymethylene diphosphonate bone imaging [60].…”
Section: Emerging Techniques and Markers To Facilitate Molecular Imagmentioning
confidence: 99%